A first exploration of a social identity perspective on youth rugby talent development in Ireland - Burrows, E.; Lyons, D.; Young, T. (Frontiers in Sports and Active Living, 2026)
This study uses a social identity perspective to explore the possible relationships between athletic identity, social identities in sport, and players` life satisfaction and confidence in managing their social groups. We report cross-sectional data from 27 of the 64 early-career academy-contracted rugby players in Ireland in 2025. Exploratory analyses indicate that players endorsed stronger identification with their sport and their club than with a singular athletic identity. Importantly, life satisfaction was positively associated with their confidence in managing multiple social groups but not the strength of their athletic identity. This is consistent with the social identity model of identity change (SIMIC), which posits that belonging to multiple social groups and managing these identities effectively supports well-being during transitions, such as progressing into professional sport. This perspective suggests that fostering early-career athletes` confidence to balance and maintain diverse social identities including family, education, and friendships, may support their well-being.